Global Marketing Strategy of Indomie in Facing Competition in the Nigerian Market - Muhammad Rifqi Salichin; Moza Muhammad Althaf; Mochamad Zidane Farrel Dermawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the global marketing strategy of Indomie, a flagship instant noodle product of PT Indofood Sukses Makmur, in penetrating and sustaining its competitive position in the Nigerian market. Nigeria represents one of the most strategically significant international markets for Indomie, where the brand has achieved a level of cultural embedding so deep that Nigerian consumers frequently use